Effect of Low-Intensity Interval Training on Physical Performance and Blood Parameters Among Junior Handball Players - Marai, Rasmi; Triki, Raoua; Bougrine, Houda; Hammami, Amri; Khalfoun, Jihen; Baaziz, Mohamed; Abderrahman, Abderraouf Ben (Advances in Social Sciences Research Journal, 2024)
The purpose of this study is to investigate the effect of low-intensity interval training program (LIIT) on physical fitness and blood parameters among junior handball players. Thirty young players participated in this study and were divided into two groups: an experimental group (n=15) which underwent a low-intensity interval training program, and a control group (n=15) which underwent a traditional training program. Blood parameters (hemoglobin (g/dl), mean corpuscular hemoglobin MCH (pg), and hematocrit (%)) and physical capacities (flexibility, speed, endurance, agility, upper body muscle strength, and power) were evaluated before and after eight weeks of training in the two groups. At the beginning and end of the eight-week program, significant differences between the groups were observed. The experimental group exhibited better development compared to the control group in the following parameters: endurance (2.77%, p=0.03), speed (6.8%, p=0.001), power (17.09%, p=0.02), agility (4.22%, p=0.01), flexibility (29.25%, p=0.01), and upper body strength capacity (8.82%, p=0.02). The MCH was significantly higher in the experimental group (p=0.01). However, no significant differences were observed for hemoglobin and hematocrit (p>0.05). Our findings demonstrate that the low-intensity interval training intervention was more effective than the traditional program in improving physical parameters and mean corpuscular hemoglobin. The suggested low-intensity interval training program could serve as a viable fitness strategy for aerobic sports.